Myonecrosis in a Sickle Cell-Diseased Patient: A Case Report and Literature Review - Ali Wasel Almomen; Yaser Mansour Tawfeeq; Ahmed Khalid Almuhaisin; Abdulraheem Ayman Altalib (Case Reports in Orthopedics)
Myonecrosis is a condition that results in muscle tissue necrosis, and it is rarely seen in sickle cell patients and often missed because more common manifestations of sickle cell can overlap like vaso-occlusive crises (VOC), which results in pain in the extremities or spine; also osteomyelitis is commonly seen in sickle cell patients. In this article, we present a case of myonecrosis in a sickle cell-diseased patient who presented with left acute atraumatic left foot pain and MRI with contrast showing characteristic image of muscle infarction supportive therapy initiated, and 2-year follow-up did not reveal any physical disabilities; further study and follow-up are needed to know the nature of the disease and avoid improper management of those patients.